Diagnostic Assessment In Implementing Curriculum Merdeka On Senior High School - Aringka, Yanche; perpisa, Lili; Siska, Siska (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to examine the implementation of diagnostic assessment in the independent curriculum at SMA N 1 Sitiung. This research utilizes a Descriptive method with a Qualitative approach. The participants in this study are two English language teachers in the E phase at SMAN 1 Sitiung. Data were collected from these two English language teachers through audio-recorded interviews. The researcher employed nine research questions using indicators from the diagnostic assessment implementation stage to understand how assessment is conducted by English language teachers. Based on the research findings, it was discovered that diagnostic assessment plays a crucial role for teachers in identifying students' weaknesses and challenges. In terms of implementation, it aligns with the procedures for applying diagnostic assessment to students in English language learning. However, based on data collected through teaching modules, diagnostic assessment results for students, and interview transcripts, it was found that teachers are effectively applying diagnostic assessment in accordance with the existing procedures to identify weaknesses and measure students' abilities.